1987
DOI: 10.1007/bf02442855
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Richardson extrapolation in simulation studies of EEGs

Abstract: I n t r o d u c t i o nTo BE ABLE to compute the potential distribution on the scalp due to brain activity (as reflected in EEGs) and the distribution of a component of the magnetic field (as reflected in MEGs), both the source and the volume conductor (i.e., the head) have to be modelled. Dipolar current sources are commonly used as a model for brain activity.In the past it was common practice to describe the head by models for which an analytical solution exists. Usually, the head is described by a set of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…However, modeling the head by a poor conductor (the skull) between two much better conductors (the brain tissue and the scalp) requires modifications in the standard numerical approach in order to produce accurate results. Meijs and Peters (1987) found that numerical errors in computing V may be excessive because the ratio in the conductivity of the skull to that of the brain and the scalp is less than 0.1. The first suggested solution for this numerical instability was the use of the Richardson extrapolation (Richardson and Guant, 1927;Meijs, Peters, et al , 1987).…”
Section: Realistically Shaped Conductor Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, modeling the head by a poor conductor (the skull) between two much better conductors (the brain tissue and the scalp) requires modifications in the standard numerical approach in order to produce accurate results. Meijs and Peters (1987) found that numerical errors in computing V may be excessive because the ratio in the conductivity of the skull to that of the brain and the scalp is less than 0.1. The first suggested solution for this numerical instability was the use of the Richardson extrapolation (Richardson and Guant, 1927;Meijs, Peters, et al , 1987).…”
Section: Realistically Shaped Conductor Modelsmentioning
confidence: 99%
“…Meijs and Peters (1987) found that numerical errors in computing V may be excessive because the ratio in the conductivity of the skull to that of the brain and the scalp is less than 0.1. The first suggested solution for this numerical instability was the use of the Richardson extrapolation (Richardson and Guant, 1927;Meijs, Peters, et al , 1987). This approach relies on the assumption that the correct potential distribution can be obtained by estimating an asymptote on the basis of two solutions with different grid densities.…”
Section: Realistically Shaped Conductor Modelsmentioning
confidence: 99%
“…However, this procedure leads to a practical problem since the number of discrete points needed to obtain an accuracy of 5% in the final field distribution would result in a CPU time in the order of 200 h for the DEC-20 computer used for the computations. The amount of computational work can be substantially decreased by making use of the Richardson extrapolation technique, as described elsewhere (Meijs et al 1987). Nevertheless, the present study demonstrates the usefulness of the new model of the volume conductor.…”
Section: Modelmentioning
confidence: 91%
“…If one of the components inside the volume conductor has a relatively low conductivity compared with the conductivities of the other components, the numerical errors have been shown to be blown up [ 5 ] , [ 8 ] . Let us assume that only one compartment inside the volume conductor has a relatively low conductivity, not being the outer shell, i.e., the ( m -1 )th compartment of the volume conductor consisting of N ( N > 2 ) , nested, compartments ( N I m , Fig.…”
Section: The Isolated Problem Approachmentioning
confidence: 99%
“…However, during simulation studies using a head model consisting of four realistically shaped compartments, the discrete boundary element (BE) method used to compute the EEG's was found to generate numerical errors, which were blown up due to the small conductivity of the skull [5]. To study this problem, simulations of EEG's based on the four concentric spheres model were carried out by means of the BE method.…”
Section: Introduction or A Quantitative Interpretation Of Electroementioning
confidence: 99%